2014
DOI: 10.1097/mib.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Repetitive Ileocolic Resection in Patients with Crohnʼs Disease

Abstract: Immunomodulators have a protective impact regarding surgical recurrence after ICR. In contrast, ileal disease location constitutes a significant risk factor for a second ICR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…There was no difference in the proportion of Non-IBD (n=32) and CD (n=36) samples that passed quality control ( P =.4747 by Fisher’s exact test). The demographic data for these CD subjects were comparable to the spectrum of data previously reported 23, 24 (Table S1). The average age at the time of surgery was significantly different between the Non-IBD and CD groups (Table S1); however, no significant differences in transcript abundances were identified within either diagnosis group based on this variable.…”
Section: Resultssupporting
confidence: 79%
“…There was no difference in the proportion of Non-IBD (n=32) and CD (n=36) samples that passed quality control ( P =.4747 by Fisher’s exact test). The demographic data for these CD subjects were comparable to the spectrum of data previously reported 23, 24 (Table S1). The average age at the time of surgery was significantly different between the Non-IBD and CD groups (Table S1); however, no significant differences in transcript abundances were identified within either diagnosis group based on this variable.…”
Section: Resultssupporting
confidence: 79%
“…Small bowel involvement negatively affects the long-term outcome of CD but is less associated with C-reactive protein and fecal calprotectin[36]. Ileal involvement in patients with CD is a significant risk factor[7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors of the former study, this could be partially explained by the small number of patients recruited (n=127), including only 15% smokers. As for the latter, this result could be explained by the lack of 23% and 16% of smoking data at diagnosis and follow up respectively [ 43 , 44 ].…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…It has been evaluated in several studies, but outcomes are conflicting. Searching the literature, we found studies demonstrating either male [ 49 ] or female [ 50 ] sex as a predictive factor for POR, whereas the majority of authors found no differences in recurrence rates [ 43 , 44 , 51 , 52 ].…”
Section: Patient-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation